2020
DOI: 10.1155/2020/8824150
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Molecular Mechanism of Qing Guang An Granule in Treating Glaucoma Using Network Pharmacology and Molecular Docking

Abstract: Background. Qing Guang An Granule (QGAG), a Chinese patent medicine, has been used clinically to treat glaucoma for more than 20 years. Objective. To explore the possible mechanism of treatment of QGAG in glaucoma by using network pharmacology and molecular docking in this study. Methods. Active compounds and targets of each herb in QGAG were retrieved via the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP). Glaucoma-related targets were acquired from OMIM and DisGeNET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…However, applying network pharmacology in studying ophthalmic diseases and ophthalmic herbs is very rare. The results of network pharmacology confirm that Qing Guang An Granule regulates p53, HIF-1, PI3K-Akt, and neurotrophin signaling pathways to treat glaucoma, which is similar to our results [ 32 ]. VEGFA, AKT1, and IL-6 were recognized as core targets in the network pharmacology prediction study of Astragalus membranaceus in treating the diabetic retinopathy, and the PI3K-Akt signaling pathway role has also been highlighted [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, applying network pharmacology in studying ophthalmic diseases and ophthalmic herbs is very rare. The results of network pharmacology confirm that Qing Guang An Granule regulates p53, HIF-1, PI3K-Akt, and neurotrophin signaling pathways to treat glaucoma, which is similar to our results [ 32 ]. VEGFA, AKT1, and IL-6 were recognized as core targets in the network pharmacology prediction study of Astragalus membranaceus in treating the diabetic retinopathy, and the PI3K-Akt signaling pathway role has also been highlighted [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…7-O-Methylisomucronulatol was key compound in the compound-target network of Qing Guang An Granule (QGAG) to the treatment of glaucoma [ 36 ]. Scutellarin was discovered as a substance that protects the nerves of the eyes and brain, which is a new neurotherapeutic agent for glaucoma treatment, it has been studied in mice, at present, [ 37 , 38 ]. Acetylsalicylic acid has complex effects on the changes of intraocular pressure, studies have demonstrated that single-use of acetylsalicylic acid cannot significantly reduce intraocular pressure in glaucoma patients, but long-term use will have an impact on intraocular pressure [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…)), Chi-shao-yao 10g ( Paeoniae Radix Rubra ; Paeonia lactiflora Pall ), Hong-hua 5g ( Carthami Flos ; Carthamus tinctorius L) and Di-long 10g ( Lumbricus ; Lumbricus terrestris ) to boost Qi, nourish Yin, activate blood and dredge meridians. 13 It was developed by the First Affiliated Hospital of Hunan University of Chinese Medicine, and has been widely used in clinical care for over 20 years. Long-term clinical observation showed it inhibited scarring with less complications than intraoperative application of (mitomycin C), a common antimetabolite used in GFS, 14 and researches supported it can obviously lower , reduce sub-conjunctival fibroblast proliferation as well as protect RGCs (retinal ganglion cells).…”
Section: Introductionmentioning
confidence: 99%